2018
DOI: 10.1016/j.molp.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Pandemonium Breaks Out: Disruption of Salicylic Acid-Mediated Defense by Plant Pathogens

Abstract: Salicylic acid (SA) or 2-hydroxybenoic acid is a phenolic plant hormone that plays an essential role in plant defense against biotrophic and semi-biotrophic pathogens. In Arabidopsis, SA is synthesized from chorismate in the chloroplast through the ICS1 (isochorismate synthase I) pathway during pathogen infection. The transcription co-activator NPR1 (Non-Expresser of Pathogenesis-Related Gene 1), as the master regulator of SA signaling, interacts with transcription factors to induce the expression of anti-micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 166 publications
4
72
0
1
Order By: Relevance
“…Downregulation of SA biosynthesis genes can be explained by two hypotheses: SA level in both stages evaluated in this work is high, thus the expression of ICS1 and PAL genes is low because SA synthesis is no more necessary or ICS1 is potentially targeted by CaL. to suppress SA-mediated plant immunity, as showed to other plant pathogens (Qi et al, 2018). For SA metabolism, BSMT1 (BENZOIC ACID/SALICYLIC ACID CARBOXYL METHYLTRANSFERASE1) -a SA metabolic enzyme gene -had significant level of induction in late stage of infection of both CLas and CLam (Figure 2).…”
Section: Microscopical Analysesmentioning
confidence: 86%
See 2 more Smart Citations
“…Downregulation of SA biosynthesis genes can be explained by two hypotheses: SA level in both stages evaluated in this work is high, thus the expression of ICS1 and PAL genes is low because SA synthesis is no more necessary or ICS1 is potentially targeted by CaL. to suppress SA-mediated plant immunity, as showed to other plant pathogens (Qi et al, 2018). For SA metabolism, BSMT1 (BENZOIC ACID/SALICYLIC ACID CARBOXYL METHYLTRANSFERASE1) -a SA metabolic enzyme gene -had significant level of induction in late stage of infection of both CLas and CLam (Figure 2).…”
Section: Microscopical Analysesmentioning
confidence: 86%
“…However, MeSA seems not to be the only molecule essential to establish SAR (Attaran et al, 2009;Zheng et al, 2012;Maruri-López et al, 2019), and several candidate molecules have been suggested (Shah & Zeier, 2013). Moreover, some pathogens manipulate phytohormone pathways, converting SA to inactive derivatives as MeSA, to bypass defenses responses (Cui et al, 2005;Qi et al, 2018). In A. thaliana, Pseudomonas syringae prevents the SA accumulation by inducing the SA metabolic gene BSMT1 and repressing SA synthesis gene ICS1, similar to what was observed in late stages of CLam inoculated-citrus plants (Table 2).…”
Section: Microscopical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…One pathway converts chorismate to isochorismate via isochorismate synthase (ICS1) in the chloroplast with subsequent conversion of isochorismate to SA in the cytosol [15]. A second pathway accounts for~10% of SA synthesis by converting isochorismate to SA via the phenylalanine ammonia-lyase pathway in the cytosol [3,4,8,15,16]. Phenylalanine is also synthesized in the chloroplast from chorismate [5].…”
Section: An Overview Of Chloroplast Contributions To Plant Immunitymentioning
confidence: 99%
“…In the absence of SA, oligomerized NPR1 proteins are retained in the cytoplasm, but SA-activated NPR1s are reduced together with cellular redox changes, monomerized, and translocated to the nucleus. Monomeric NPR1 does not exhibit DNA-binding activity as a TF; instead, it regulates target genes by interacting with a wide range of transcription activators, repressors, and cofactors that include members of the WRKY and bZIP transcription factor TGA families as well as NIM1-interacting proteins (NIMINs) [57,58]. NPR1 was proposed to regulate the transcription of PR genes together with the TGA family TF as a cofactor [59].…”
Section: How Are Atr8 and Wrky70 Expression Regulated By Sa?mentioning
confidence: 99%